LEAN SUPPLY CHAIN UNTUK MENINGKATKAN EFISIENSI SISTEM MANUFAKTUR PADA PT. XYZ - Iveline Anne Marie; Dedy Sugiarto; Dara Mustika (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2017)
There were wastes in the supply chain flow of PT. XYZ which leads to long lead time in the delivery of customer orders. The result is that the company's planned delivery targets are not fulfilled. The objective of this research is to identify waste and cause of waste and to propose improvement to eliminate waste in PT XYZ supply chain so as to reduce lead time and achieve delivery target as an effort to improve company performance with Lean Supply Chain approach. In this research we use VALSAT to minimize waste and non value added activities in supply chain flow. Based on Value Stream Mapping and analysis of waste we proposed improvements that is application of acceptance sampling method on raw material inspection, application of p control chart on assembling process and store warehouse, 2 days battery storage time limit with kanban card proposed and also change of process sequence of lead part casting. Based on the projection, we got the decrease of manufacturing lead time and the increase of process cycle efficiency from 51.47% to 73.69%.